Acupuncture for menstruation-related migraine prophylaxis: A multicenter randomized controlled trial - Liu, Lu; Zhang, Claire-Shuiqing; Liu, Hui-Lin; He, Fan; Lyu, Tian-Li; Zeng, Lin; Zhao, Luo-Peng; Wang, Mi-Na; Qu, Zheng-Yang; Nie, Li-Min; Guo, Jia; Zhang, Xiao-Zhe; et al. (Frontiers in Neuroscience, 2022)
Objective: The aim of this study was to evaluate the efficacy of acupuncture, an alternative medicine therapy, as a preventive treatment for menstruation-related migraine (MRM). Patients and Methods: This was a prospective, multicenter, double-dummy, participant-blinded, randomized controlled clinical trial conducted in China between April 1, 2013, and April 30, 2014. The participants were enrolled from four study centers and randomized to into either the acupuncture group, which received 24 sessions of acupuncture at traditional acupoints plus placebo, or the medication group, which received sham acupuncture plus naproxen. The primary endpoint was change from the baseline average number of migraine days per perimenstrual period over cycles 1-3. The secondary endpoints included changes from the baseline average number of migraine days outside the perimenstrual period, mean number of migraine hours during and outside the perimenstrual period, mean visual analogue scale score during and outside the perimenstrual period, ≥50% migraine responder rate, and the proportion of participants who used acute pain medication over cycles 1-3 and 4-6. Results: A total of 172 women with MRM were enrolled; 170 in the intention-to-treat analyses. Our primary outcome reported a significant between-group difference that favored the acupuncture group (95% CI, 0.17–0.50; P<.001), with the average reduction of migraine days per perimenstrual period from the baseline was 0.94 (95% CI, 0.82–1.07) in the acupuncture group and 0.61 (95% CI, 0.50–0.71) in the medication group over cycles 1-3. Conclusions: This study showed that compared to medication, acupuncture reduces the number of migraine days experienced by patients with MRM. For patients who received the acupuncture treatment over three cycles, the preventive effect of the therapy was sustained for six cycles.